(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the current status of the quality of social work services supporting patients at Thu Duc General Hospital, Ho Chi Minh City, in 2025-2026. Methods: A cross-sectional descriptive study was conducted on 364 patients and/or their caregivers at Thu Duc General Hospital in 2025-2026. Data were collected using a structured questionnaire and secondary data from hospital social work reports, and analyzed using descriptive statistics. Results: Social work activities at the hospital were relatively comprehensive, with the participation of 1,230 volunteer participations annually. Material support activities were implemented on a large scale, including 32,890 free meal servings, 7,510 instances of financial support for living expenses, and 1,297 cases of treatment cost assistance. The majority of participants were under 60 years old (75.00%), female (60.99%), and from Ho Chi Minh City (74.73%). Frequently provided services included navigation guidance and free meal provision (63.19%), and psychological support (58.52%). The highest demand for counseling was related to healthcare procedures (81.87%) and health insurance policies (78.85%). The proportion of respondents rating needs as “very necessary” ranged from 63.19% to 64.29%. Overall satisfaction reached 82.42%, with 48.35% satisfied and 34.07% very satisfied. Conclusion: Social work services at the hospital have been implemented relatively comprehensively, with effective resource mobilization and support activities. The high satisfaction rate (82.42%) indicates initial effectiveness; however, further improvements in service quality are still needed.